2010
DOI: 10.1177/0959683609354302
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotopes as potential sea-level indicators in salt marshes, North Carolina, USA

Abstract: We compared the use of δ 13 C values and C:N ratios from salt-marsh sediments to reconstruct relative sea level (RSL) with an established approach using foraminifera. Analysis of bulkorganic sediment and plant samples collected along transects at two sites in North Carolina, USA demonstrates that sediment δ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 65 publications
2
49
1
Order By: Relevance
“…In North Carolina, sediments under Spartina alterniflora have been associated with δ 13 C values of between -18.6‰ and -14.0‰ (Craft et al, 1988;Currin et al, 1995;Kemp et al, 2010). Similar sediments in South Carolina had δ…”
Section: Values In Bulk Surface Sedimentsmentioning
confidence: 72%
See 3 more Smart Citations
“…In North Carolina, sediments under Spartina alterniflora have been associated with δ 13 C values of between -18.6‰ and -14.0‰ (Craft et al, 1988;Currin et al, 1995;Kemp et al, 2010). Similar sediments in South Carolina had δ…”
Section: Values In Bulk Surface Sedimentsmentioning
confidence: 72%
“…widely recognized (Haines, 1976;Ember et al, 1987;Benner et al, 1991). In North Carolina, Spartina sediments up to 6.4‰ more depleted than corresponding plants have been reported (Craft et al, 1988;Kemp et al, 2010). Similarly, Goni and Thomas (2000) showed a difference of 4.0‰ to 6.8‰ in South Carolina.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These C values was up to 60% better than using 556 foraminifera alone (Cahill et al, 2016). In contrast, a similar study in North Carolina concluded that 557 bulk-sediment δ 13 C values could not be objectively used as a sea-level indicator because the monospecific 558 high salt-marsh zone is vegetated by the C3 species Juncus roemerianus, making it indistinguishable from 559 a freshwater upland (Kemp et al, 2010). 560…”
Section: Distribution Of Testate Amoebae 481mentioning
confidence: 86%